Dampak Pengawasan Dan Pembagian Kerja Terhadap Kinerja Karyawan OS (Out Source) Melalui Disiplin Kerja PT. PLN (Persero) Unit Layanan Pelanggan Medan Selatan - Pohan, Nadhiva Nurhaliza; Hafizah, Hafizah; Syafi’i, Indra (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to determine the effect of supervision on work discipline. To determine the effect of the division of labor on work discipline. To determine the effect of supervision on employee performance. To determine the effect of the division of labor on employee performance. To determine the effect of work discipline on employee performance. To determine the effect of supervision on employee performance through work discipline. To determine the effect of division of labor on employee performance through work discipline. The total population in this study amounted to 95 people. The samples taken in this study were all employees because the population was less than 100 so all of them were sampled or also called saturated samples. The data collection technique used in this study was through a questionnaire. The results showed that supervision had no significant effect on work discipline, the division of labor had a positive and significant effect on work discipline, supervision had a positive and significant effect on employee performance, and the division of labor had no significant effect on employee performance. Work discipline has a positive and significant effect on employee performance, there is a positive and significant influence on supervision on employee performance through work discipline and there is a significant influence on the division of labor on employee performance through work discipline.